Modern molecular and biological aspects of endometriosis-associated infertility - Anastasiia S Safronova; Mikhail Yu Vysokikh; Vladimir D Chuprynin; Natalia A Buralkina (IP Berlin A.V., 2019)
There is currently no consensus on the etiopathogenetic nature of endometriosis. The causes of aggressive, progressive, infiltrative growth of endometrioid tissue also remain unclear. An important problem remains the high recurrence rate of endometriosis, despite the availability of modern drug and surgical methods of treatment. The study of the central signaling pathways and the search for new key molecules is of paramount importance for a better understanding of the pathogenesis of the disease, and is also an important step in the development of new strategies for the diagnosis, prevention and treatment of endometriosis.